(untitled) (Khairulummah, 2022)
This study has made an analysis of the Afghan refugees’ literature during the period of one decade from 1979 to 1989, the time of Soviet invasion of Afghanistan. The period of that one decade, when there was the tumult and crisis of war, millions of Afghans were forced to flee away from their homeland to other lands, including Iran, Europe, USA, Germany and Pakistan. The larger number of Afghan refugees came for shelter to the Khyber Pakhtunkhwa province of Pakistan, which included different classes of the Afghan society. There were poets, writers, intellectuals, researchers and university teachers amongst those almost three million refugees, who continued with their writings and different literary activities, mostly in Peshawar. The study covers the writings of Peshawar-based Afghan refugees, with dominant Diasporic elements, as the tragedy was not an ordinary one, over which writers continue to write even today and will continue to write in future. Diaspora is a significant phenomenon in the history of many nations, which always leave a profound impact on the thinking and outlook of its ordinary masses and also on its writers and poets. The tragedy of homeless people is beyond measure as homelessness is followed by numerous issues with refugees everywhere in the world. The Afghan refugees were also confronted with the universal Diasporic issues, which is clearly perceptible in the writings of Afghan Diasporic poets and writers. The Afghan Diaspora had another important aspect as well. The refugees in Khyber Pakhtunkhwa were either pro-communism or anti-communism. The refugees, who were anti-communism, were larger in number, so, during the Afghan Jihad against communism, the anti-communists promoted Jihadi propaganda, thus producing Jihadi literature. The study covers the analysis of the poetry, prose and jihadi literature of the Afghan Diaspora during the decade of 1979 to 1989.